1988
DOI: 10.1002/ccd.1810140305
|View full text |Cite
|
Sign up to set email alerts
|

Thromboembolic complications in coronary angiography associated with the use of nonionic contrast medium

Abstract: Thromboembolic complications occurred during diagnostic coronary arteriography in three patients in spite of systemic heparinization. These mishaps were associated with the use of a nonionic contrast medium, which is known not to have a significant protective effect on coagulation pathways. If nonionic contrast media are to be used in angiographic studies of critical organs, meticulous technique is imperative, and adequate systemic heparinization is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

1989
1989
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(19 citation statements)
references
References 21 publications
1
18
0
Order By: Relevance
“…23,24 In our study, mean hemoglobin concentration and WBC and platelet counts decreased significantly after iopamidol injection. This could be interpreted as hemodilution, activity of adhesion molecules together with the WBCs, and consumption of platelets for clot or thrombus formation during procedures, 22 which support the findings of Belleville et al 20 Also, contrast material may modify CFI and/or its binding to the platelets, thereby changing platelet aggregation. 25,26 Platelet degranulation induced by nonionic contrast agents occurs despite the use of aspirin or heparin, and this degranulation augments the role of platelets in the activation of thrombin.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…23,24 In our study, mean hemoglobin concentration and WBC and platelet counts decreased significantly after iopamidol injection. This could be interpreted as hemodilution, activity of adhesion molecules together with the WBCs, and consumption of platelets for clot or thrombus formation during procedures, 22 which support the findings of Belleville et al 20 Also, contrast material may modify CFI and/or its binding to the platelets, thereby changing platelet aggregation. 25,26 Platelet degranulation induced by nonionic contrast agents occurs despite the use of aspirin or heparin, and this degranulation augments the role of platelets in the activation of thrombin.…”
Section: Discussionsupporting
confidence: 66%
“…21 Thromboembolic events during catheterization might be associated with the use of nonionic contrast material. 22 Several studies showed that no clotting occurred in a bolus of whole blood. 23,24 In our study, mean hemoglobin concentration and WBC and platelet counts decreased significantly after iopamidol injection.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] Although in vitro studies have shown that nonionic low osmolar agents possess less antithrombotic activity than do ionic contrast media, the effects on platelet aggregation among various nonionic contrast media have not been fully investigated. In this study blood samples from aorta through a catheter before and after left ventriculography were collected.…”
mentioning
confidence: 99%
“…Individual SCX fractions containing 10 μg of protein material are injected and captured onto a 0.3×5-mm trap column (3-μm C 18 (Dionex-LC Packings, Hercules, CA)) and then eluted onto a 75 μm×15 cm Pepmap analytical column (5-μm C 18 (Dionex-LC Packings)) using a binary gradient (200 nl/ min) from 5% to 45% buffer B with mobile phase A 2% ACN, 0.1% TFA, and mobile phase B 85% ACN, 5% isopropanol, 0.1% TFA). For MALDI MS/MS analysis, column effluent is mixed in a 1:2 ratio with MALDI matrix (7 mg/ml cyano-4-hydroxycinnamic acid) through a 25-nl mixing tee (Upchurch Scientific, Oak Harbor, WA) and spotted in 192 spot arrays.…”
Section: Lc-ms Analysismentioning
confidence: 99%
“…Studies evaluating the effects of RCM on the cellular components of blood [3][4][5][6][7][8] and vascular endothelium [9,10] have produced inconclusive and conflicting results with, consequently, unclear clinical relevance. Despite the overall safety profile documented by large-scale studies of contrast agents [11,12], there continues to be controversy surrounding the proinflammatory [13][14][15] and pro-thrombotic potential of RCM [16][17][18]. The increasing number of high-risk patients undergoing diagnostic and therapeutic procedures increases the potential for higher rates of adverse effects associated with RCM.…”
Section: Introductionmentioning
confidence: 99%